Analyses of case-based surveillance data on malaria in pregnancy in Plateau State, Nigeria 2013–2017. (June 2021) - Iyare, Osarhiemen; Adebowale, Ayo Stephen; Umeokonkwo, Chukwuma David; Bamgboye, Eniola Adetola; Gobir, Abdullahi Abdulrazaq; Chikan, Jiwok Joseph; Dahiru, Tukur; Ajayi, IkeOluwapo Oyeneye
Background: Malaria in pregnancy accounts for 11% of maternal death in Nigeria. Plateau State has a low uptake of intermittent preventive treatment of malaria among women attending antenatal care. Objectives: This study examined the trend and made projections of reported cases of malaria in pregnancy in Plateau State. Methods: Data were extracted from the state disease surveillance system from January 2013 to December 2017. Reported cases of malaria in pregnancy within the 5 years under investigation were retrieved, merged and sorted by month of reporting and Local Government Area (LGA). Prevalence was calculated yearly for each LGA in Plateau State using Geographic Information System. Seasonal variation and projection were based on a multiplicative time series model. Results: In total, 62, 997 cases of malaria in pregnancy were retrieved. Prevalence was 6.9% in 2013 and increased to 15.1% in 2017. Higher prevalence was observed in Wase, Kanam and Shendam LGAs. A cyclical trend with highest number of malaria in pregnancy cases was found within the third quarter of all the years. Within the 5 years, there was higher seasonal variation for quarters three (1.209834) and one (1.099711). The highest number of cases of malaria in pregnancy was likely to occur in the third quarter, while the least was found in the second quarter. The projected numbers of malaria in pregnancy cases are 20, 121, 22, 593 and 25, 064 for year 2018, 2019 and 2020, respectively, and the highest number of cases occurs in the third quarter. Conclusion: Malaria in pregnancy follows an increasing trend in Plateau State, with greatest severity in the third quarter of the year. An effective intervention strategy against malaria among pregnant women is advocated.